THE PERFORMANCE REPUTATION OF BANK BTPN SYARIAH AND BANK MUAMALAT USES COMPARATIVE ANALYSIS WITH CAMEL AND RGEC MODELS - Muhlis; Nursarita (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
Using CAMEL and RGEC analytical models, this study aims to describe the reputation of BTPN Syariah compared to Muamalat Bank and to ascertain whether the financial performance and reputation of Indonesian Muamalat Banks and BTPN Syariah differ significantly. This study uses a quantitative descriptive method; that is, it describes the health of the Islamic banking industry based on the figures provided. This study shows that (1) the health assessment using CAMEL and RGEC methods leads to very different results. During 2018–2022, the health status of Bank BTPN Syariah using the CAMEL method showed good health status, while the health status of Bank Muamalat Indonesia using both methods showed excellent health status. Using the CAMEL and RGEC analysis models, it was found that there is a significant difference between the financial performance reputation of Bank BTPN Syariah and Bank Muamalat Indonesia. Based on the Mann Whitney U test, it was found that in the column Asymp.Sig. (2-tailed) for the CAMELS and RGEC tests is 0.027 or a probability less than 0.05 (0.027 < 0.05), indicating that there is a difference in the assessment of the level of health.